Performance of the St George's Respiratory Questionnaire in patients with connective tissue disease‐associated interstitial lung disease. Issue 9 (25th March 2018) - Suzuki, Atsushi; Kondoh, Yasuhiro; Swigris, Jeffrey J.; Ando, Masahiko; Kimura, Tomoki; Kataoka, Kensuke; Yamano, Yasuhiko; Furukawa, Taiki; Numata, Mari; Sakamoto, Koji; Hasegawa, Yoshinori
ABSTRACT: Background and objective: The St George's Respiratory Questionnaire (SGRQ) is a self‐administered questionnaire used to assess health‐related quality of life (HRQoL) in various chronic respiratory diseases. Few studies have assessed the performance of the SGRQ in patients with connective tissue disease‐associated interstitial lung disease (CTD‐ILD). We aimed to examine the SGRQ's performance characteristics and generate data to support its reliability and validity in patients with CTD‐ILD. Methods: We used data from 193 CTD‐ILD patients evaluated at Tosei General Hospital from May 2007 to July 2016 to assess the cross‐sectional and longitudinal validity of the SGRQ. Results: The mean age of the patients was 64.2 years and 122 (63.2%) were women. There were no significant differences in SGRQ scores between any of the CTD groups. Internal consistency (Cronbach's α = 0.905) and repeatability (intraclass correlation coefficient (ICC) = 0.873) for the SGRQ total score were excellent. At baseline, SGRQ total score was significantly associated with clinically meaningful measures of physiological function, exercise capacity and dyspnoea. Change in SGRQ total score over 6 months was also associated with change in other measures. Cox proportional hazards models showed that higher baseline SGRQ total score was a significant predictor of mortality. The estimated minimal clinically important difference of SGRQ total score was 4–13 points. Conclusion: These data support the validity and reliability of SGRQ as a sensitive measure for capturing HRQoL in patients with CTD‐ILD. Abstract : This research study supports the validity and reliability of the St George's Respiratory Questionnaire (SGRQ) as a sensitive measure for capturing health‐related quality of life in patients with connective tissue disease‐associated interstitial lung disease (CTD‐ILD). See related Editorial